Cardiac Resynchronization Therapy Reduces Subcellular Heterogeneity of Ryanodine Receptors, T-Tubules, and Ca2+ Sparks Produced by Dyssynchronous Heart Failure. (November 2015) - Li, Hui; Lichter, Justin G.; Seidel, Thomas; Tomaselli, Gordon F.; Bridge, John H.B.; Sachse, Frank B.
Abstract : Background—: Cardiac resynchronization therapy (CRT) is a major advance for treatment of patients with dyssynchronous heart failure (DHF). However, our understanding of DHF-associated remodeling of subcellular structure and function and their restoration after CRT remains incomplete. Methods and Results—: We investigated subcellular heterogeneity of remodeling of structures and proteins associated with excitation–contraction coupling in cardiomyocytes in DHF and after CRT. Three-dimensional confocal microscopy revealed subcellular heterogeneity of ryanodine receptor (RyR) density and the transverse tubular system (t-system) in a canine model of DHF. RyR density at the ends of lateral left ventricular cardiomyocytes was higher than that in cell centers, whereas the t-system was depleted at cell ends. In anterior left ventricular cardiomyocytes, however, we found a similar degree of heterogeneous RyR remodeling, despite preserved t-system. Synchronous heart failure was associated with marginal heterogeneity of RyR density. We used rapid scanning confocal microscopy to investigate effects of heterogeneous structural remodeling on calcium signaling. In DHF, diastolic Ca 2+ spark density was smaller at cell ends versus centers. After CRT, subcellular heterogeneity of structures and function was reduced. Conclusions—: RyR density exhibits remarkable subcellular heterogeneity in DHF. RyR remodeling occurred in lateral and anterior cardiomyocytes, but remodeling of t-system was confined to lateral myocytes. These findings indicate that different mechanisms underlie remodeling of RyRs and t-system. Furthermore, we suggest that ventricular dyssynchrony exacerbates subcellular remodeling in heart failure. CRT efficiently reduced subcellular heterogeneity. These results will help to explain remodeling of excitation–contraction coupling in disease and restoration after CRT. Abstract : Supplemental Digital Content is available in the text.